6y+23=47

Simple and best practice solution for 6y+23=47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+23=47 equation:



6y+23=47
We move all terms to the left:
6y+23-(47)=0
We add all the numbers together, and all the variables
6y-24=0
We move all terms containing y to the left, all other terms to the right
6y=24
y=24/6
y=4

See similar equations:

| 4y+35=63 | | −x−24=5+x | | 4c=–6c+10 | | 2(j−4)=10 | | 4n-12=-32 | | –4=2j+–2 | | 2=7/2x | | 32r=4(8r) | | X+(x–3)+(x–65)=200 | | x^+12x+3=136 | | (12x-6)31+59=190 | | 23-5+21x+5=180 | | 1.5x-1/75=-x+8.25 | | 0=20x²-13x-15 | | -6/2+x=-8 | | 78x9394322-3-42-2344322+2342342/1=8 | | 5(3x–9+5)=25+5x | | –5−8m=9(–3m+9)+9 | | 9x^2+7x−4=0 | | 12+2x-6+x+3=180 | | 8x+4=4x–12x+12 | | 5x=20+20 | | z2-12=37 | | p•-8=-56 | | 5u-5=u+35 | | 4*x*x=28x | | |x-1|+|3x-9|=4 | | x^2–10x=0 | | 4x+15=8x-125 | | 2x+44+5x-10=90 | | 4x-5+7x-35=180 | | 3^(2x+1)=9^(3x) |

Equations solver categories